2019
DOI: 10.1007/s11829-019-09724-w
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in herbivore resistance within a strawberry crop wild relative (Fragaria vesca L.)

Abstract: To decrease the dependency on chemical pesticides, the resistance of cultivated strawberry to pests needs to be increased. While genetic resources within domesticated varieties are limited, wild genotypes are predicted to show high heritable variation in useful resistance traits. We collected 86 wild accessions of Fragaria vesca L. from central Sweden and screened this germplasm for antibiosis (pest survival and performance) and antixenosis (pest preference) traits active against the strawberry leaf beetle (Ga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 49 publications
(63 reference statements)
0
17
0
Order By: Relevance
“…Many plant species show genetic variation in their resistance responses to herbivores (e.g., Bossdorf et al, 2005;Muola et al, 2010;Weber et al, 2020). In particular, Weber et al (2020) found high variation among the plant genotypes used in this study in resistance to a more specialized and coevolved herbivore (Galerucella tenella L.). The generally high mortality of S. littoralis feeding on all the plant genotypes observed in this study may reflect this herbivore's polyphagy, and lack of evolutionary history with woodland strawberry.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Many plant species show genetic variation in their resistance responses to herbivores (e.g., Bossdorf et al, 2005;Muola et al, 2010;Weber et al, 2020). In particular, Weber et al (2020) found high variation among the plant genotypes used in this study in resistance to a more specialized and coevolved herbivore (Galerucella tenella L.). The generally high mortality of S. littoralis feeding on all the plant genotypes observed in this study may reflect this herbivore's polyphagy, and lack of evolutionary history with woodland strawberry.…”
Section: Discussionmentioning
confidence: 74%
“…Plant resistance has received more attention than plant tolerance in studies of plant defenses against insect herbivores (Karban, 2011). Many plant species show genetic variation in their resistance responses to herbivores (e.g., Bossdorf et al., 2005; Muola et al., 2010; Weber et al., 2020). In particular, Weber et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The beetles avoid laying eggs on certain host genotypes and this preference is linked to the insect's fitness. Closer to home, the metabolomic profiles of invasive populations of alien weeds in the Kruger National Park, South Africa, were shown to differ significantly from their native populations in the country of origin (Weber et al, 2019). These findings reveal that the organisms on both sides of the biological control relationship are constantly evolving, even in the notoriously stable associations that have been incorporated into biological control programmes (Müller-Schärer et al, 2020).…”
Section: Introductionmentioning
confidence: 93%
“…Alternatively, secondary metabolites similarity among potential host plants may explain host suitability of a specialised insect herbivore, sometimes more so than the phylogenetic relatedness of these particular plant species (Kergoat et al, 2005;Murphy & Feeny, 2006;Rapo et al, 2019). Weber et al (2019) have shown a population of wild strawberries to differ in their acceptability ('antixenosis' = beetle preference = acceptability) and suitability ('antibiosis' = beetle survival and performance = suitability) of the strawberry leaf beetle (Garelucella tennela L.). The beetles avoid laying eggs on certain host genotypes and this preference is linked to the insect's fitness.…”
Section: Introductionmentioning
confidence: 99%